2020
DOI: 10.1093/cvr/cvaa008
|View full text |Cite
|
Sign up to set email alerts
|

The LINC00961 transcript and its encoded micropeptide, small regulatory polypeptide of amino acid response, regulate endothelial cell function

Abstract: Aims Long non-coding RNAs (lncRNAs) play functional roles in physiology and disease, yet understanding of their contribution to endothelial cell (EC) function is incomplete. We identified lncRNAs regulated during EC differentiation and investigated the role of LINC00961 and its encoded micropeptide, small regulatory polypeptide of amino acid response (SPAAR), in EC function. Methods and results Deep sequencing of human embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 45 publications
1
37
0
Order By: Relevance
“…We have previously reported that LINC00961 locus CRISPR/Cas9 KO reduces alpha-smooth muscle actin (αSMA) cell-density in the mouse hindlimb skeletal muscle without altering capillary density. [16] Global dysfunction in EC endowment resulting in compromised development of the vascular network could limit the capacity for myocardial growth and the maintenance of functional myocardium throughout life. [20] Reduced LV volume independent of adult size in LINC00961 -/-mice suggests that the vascular influence on cardiac development requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported that LINC00961 locus CRISPR/Cas9 KO reduces alpha-smooth muscle actin (αSMA) cell-density in the mouse hindlimb skeletal muscle without altering capillary density. [16] Global dysfunction in EC endowment resulting in compromised development of the vascular network could limit the capacity for myocardial growth and the maintenance of functional myocardium throughout life. [20] Reduced LV volume independent of adult size in LINC00961 -/-mice suggests that the vascular influence on cardiac development requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were lysed with QIAzol (QIAGEN, USA), RNA extracted and qRT-PCR run as previously described. [6,16] 4…”
Section: Single Cell Rnaseq Data Miningmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the role of LINC00961 in different cancers that has been proved in previous studies, LINC00961 could play crucial roles in tumor suppression in various cancers. It has recently been determined that LINC00961 encodes a conserved polypeptide, named small regulatory polypeptide of amino acid response (SPAAR) which modulates skeletal muscle regeneration [15]. Although, the expression pattern and biological function of LINC00961 have been studied in many human cancers, to the best of our knowledge, the present study is the first project that investigates the role of this lncRNA in luminal BC so far.…”
Section: Introductionmentioning
confidence: 96%
“…Predicting which lncRNA-smORFs are translated has proven difficult, as attributes to predict protein-coding ability are ineffective on small non-canonical ORFs. A small but growing number of smORF peptides translated from lncRNAs have been found to exhibit cellular and organismal functions (Anderson et al, 2015;Chen et al, 2020;Magny et al, 2013;Pueyo & Couso, 2008;Spencer et al, 2020;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%